Promotion of Olfactory Receptor Neuron Differentiation of Olfactory Neuroepithelial Cells by Using Chitosan Solution. Issue 5 (September 2017) - Li, Sheng-Tien; Young, Tai-Horng; Lin, Chih-Feng; Huang, Tsung-Wei
Background: Olfactory dysfunction significantly influences patients' quality of life. Chitosan has been reported to support neuron and Schwann cell growth and even leads to orient axonal growth. However, researchers have yet to explore whether chitosan solution can promote differentiation of olfactory receptor neurons of the olfactory neuroepithelium and be used for treating olfactory dysfunction. Objective: To evaluate the effect of chitosan solution on the differentiation of olfactory neuroepithelial cells. Method: Olfactory neuroepithelial cells were isolated from embryonic day 17 of Wistar rats and then cultured with and without soluble chitosan for 9 days. The concentration of chitosan solution was set at 0.1 mg/mL. The effects of treatment were assessed by immunocytochemistry and Western blot after culturing. Results: The morphologic analysis indicated that olfactory neuroepithelial cells treated with chitosan exhibited bipolar shape with asymmetric processes. In addition, from days 3 to 9, the expression level of βIII tubulin gradually reduced, but the expression level of olfactory marker protein significantly rose at day 9 in the chitosan groups (p < 0.05). Importantly, chitosan-treated olfactory neuroepithelial cells expressed more signal transduction apparatuses, olfactory neuron specific-G protein and adenylate cyclase 3, than those without chitosan treatment at day 9. Western blot analysis also further confirmed the results(p < 0.05). Conclusion: Experimental results revealed that soluble chitosan promoted differentiation of olfactory neuroepithelial cells based on its role in olfactory receptor neuron differentiation, neurite outgrowth, and signal transduction apparatus expressions.